Peranan Kortikosteroid Terhadap Luaran Pasien COVID-19: Sebuah Tinjauan Literatur - Ahmad Rafid; Elly Usman; Deddy Herman (Pusat Riset dan Inovasi Nasional, 2024)
Corticosteroid is one of the COVID-19 drug agents that has a pros and cons of its use because there has been a research that shows this drug had a negative impact and also there has been a research that recommend its use.This literature study conducted to discuss about role of corticosteroid towards COVID-19 patient’s outcome. This paper is a literature review that evaluates variant journals of original research with clinical study design about role of corticosteroid towards COVID-19 patient's outcome by selecting through electronic database such as PubMed, ScienceDirect, and CENTRAL with designated keywords. There are 16 literatures of clinical study design found through PubMed, ScienceDirect, and CENTRAL. It is know that the role of corticosteroid depend on patient's clinical characteristic and time given to the patients. It can be concluded that corticosteroid had role on improving oxygenation on patients with moderate-critical symptoms, reducing mortality rate on critical patients with hyperinflammation, and reducing the lenght of stay in the hospital.